From rookeries to foraging grounds: understanding regional connectivity and genetic diversity in hawksbill turtles - Madden Hof, Christine A.; Desbiens, Amelia A.; Kinch, Jeff; Fitzsimmons, Nancy N.; Versace, Hayley; Amon, Angelique; McIntyre, Nathan; Townsend, Kathy A.; Jensen, Michael P. (Frontiers in Marine Science, 2023)
This study investigated the genetic structure, diversity, and migratory patterns of hawksbill turtles (Eretmochelys imbricata) from two nesting locations in Papua New Guinea (PNG) using mitochondrial DNA (mtDNA) sequencing and satellite telemetry. Tissue samples collected from nesting female hawksbill turtles (n=75) in PNG revealed a total of 6 haplotypes from the Conflict Group site and 5 haplotypes from Kavieng site, with the Conflict Group and Kavieng samples significantly differing from one another and all other known Asia-Pacific stocks. This finding expands our understanding of the genetic stock structure of hawksbill turtles in the Asia-Pacific region, resulting in 9 Management Units (MUs) now published. Satellite tracking of 15 hawksbill turtles revealed that all individuals migrated from the Conflict Group westerly towards foraging areas in eastern Australia (93%) and PNG (7%). With a mean migration path distance of 1241 ± 108 km, three distinct migration strategies were used by the 10 hawksbill turtles that made it to their foraging grounds in the I) eastern Torres Strait, II) Far North Queensland, and III) western PNG waters. A broad scope of home-range strategies and sizes (95% UD) were used, and in comparison to other studies further postulates that hawksbills are connected to non-specific foraging grounds associated with food source availability. This study provides for the first time in PNG essential insights into hawksbill turtle population structure and connectivity in the western Pacific region, highlighting the importance of effectively conserving and managing this critically endangered species as distinct population stocks. Furthermore, we make recommendations for national and regional conservation strategies and transboundary management to ensure the long-term survival and recovery of western Pacific’s hawksbill turtle populations.